Evaluating the Impact of Long-Term Phosphorus Placement on Corn and Soybean Rotation under Minimum Tillage System - Gustavo A. Roa; Dorivar A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2023)
Phosphorus (P) management is typically done with a focus on the long term, given its impact on soil fertility. The main objective of this study was to evaluate the effect of long-term P placement on corn and soybean yields under a minimum tillage system in Kansas. Long-term research trials were established in Scandia (irrigated field) and Ottawa (rainfed) in 2006. Fertilizer treatments were applied annually to corn, including broadcast, deep-band, and starter/deep-band at 40 lb/a of P2O5, with a control having no phosphorus fertilizer. Corn and soybean responded significantly to P fertilizer at both locations (compared to the control). In the higher-yielding Scandia location, split starter/deep-band application showed a statistically significantly higher yield than broadcast or deep-band. Yield response at the Ottawa location was similar for all the P fertilizer placements.
Keywords: Phosphorus; placement; long term; strip tillage; corn; soybean; rotation